(untitled) (Revista de Estudios Interdisciplinarios, 2024)
Aqui estão as traduções para inglês e espanhol: — **Inglês:** This study analyzes the narrative identity of an elderly female guerrilla fighter expressed through speech acts. The aim is to reflect on the processes of aging and the identities of elderly guerrilla women in contemporary times. Through oral history, we recognize the need for a listening approach in which the speech acts revealed in the voice of our narrator evoke imaginaries and representations that support the understanding and identity of the elderly woman. These combine into an assertive discourse that transforms the contemporary aging process into a polyphonic experience. The analysis seeks to relationally establish her living conditions and those of other guerrilla fighters today. Based on life conditions, her stories, and the stories of others, the behaviors assumed and aspirations expressed synthesize heterogeneous elements of womanhood, exposing the identity contradictions that form diverse social trajectories. These trajectories are circumscribed by complex networks of social relationships, where the durability of life reinvents female bodies and reinscribes characters and contradictory identities that complement each other in the continuous recomposition of different identities and various temporalities in a body that reconnects with its experiences. — **Espanhol:** Este estudio analiza la identidad narrativa de una mujer guerrillera anciana expresada en actos de habla. El objetivo es reflexionar sobre los procesos de envejecimiento y las identidades de las mujeres guerrilleras mayores en la contemporaneidad. A través de la historia oral, comprendemos la necesidad de una escucha en la que los actos de habla revelados en la voz de nuestra narradora evoquen imaginarios y representaciones que sostienen la comprensión y la identidad de la mujer mayor. Estos combinan un discurso reivindicativo que transforma el proceso de envejecimiento contemporáneo en una experiencia polifónica. El análisis procura establecer de manera relacional sus condiciones de vida y las de otras guerrilleras en la actualidad. A partir de las condiciones de vida, sus historias y las historias de otras mujeres, los comportamientos asumidos y las aspiraciones expresadas sintetizan elementos heterogéneos de la condición de ser mujer y exponen las contradicciones identitarias que forman trayectorias sociales diversas, circunscritas a redes complejas de relaciones sociales. En estas redes, la durabilidad de la vida reinventa los cuerpos femeninos y reinscribe personajes e identidades contradictorias, que se complementan en recomposiciones continuas de diferentes identidades y diversas temporalidades en un cuerpo que se reencuentra con sus experiencias.